FOREIGN DIRECT INVESTMENT AND ECONOMIC DEVELOPMENT IN SOUTH EAST GEOPOLITICAL ZONE OF NIGERIA - Anikeze, Nnaemeka Hillary; Igbokwe, Igbokwe Chukwuma (African Journal of Social and Behavioural Sciences, 2024)
The present study examined empirically Direct Foreign Investment and Economic Development in South East Geopolitical Zone of Nigeria. The specific objectives of the study are to; determine the extent foreign direct investment (FDI) have contributed on human capital in South East Geopolitical Zone of Nigeria, examine the extent foreign direct investment (FDI) have contributed on infrastructure in South East Geopolitical Zone of Nigeria. Ordinary Least Square (OLS) research design was adopted for the study. The findings of the study revealed that there is significant positive relationship between foreign direct (FDI) and human capital in South East Geopolitical Zone of Nigeria, as foreign investment led to increased economic activities in the area which on the long run led to social and economic development of the human capacity in the study areas. On the same vein, the study also revealed a positive correlation between foreign direct investments (FDI) on infrastructural development in the sense that continuous flow of foreign investment has necessitated the development of infrastructures in the study areas. Based on the findings the following recommendations were proposed; The Nigerian government should endeavour to establish favourable economic and political policies that will attract foreign investors for enhanced economic activities and diversification of the economy to ensure sustainable development across the nation, the government should provide incentive for indigenous industries to engage in international trade, as this will help create a formidable base for foreign investors looking for indigenous links.